Predictors of Acute Kidney Injury in Critically Ill Patient at Intensive Cardiac Care Unit - Jauhari, Haris; Bagaswoto, Hendry Purnasidha; Setianto, Budi Yuli (The Indonesian Heart Association, 2022)
Background: Acute kidney injury (AKI) occurs frequently in the intensive cardiac care unit (ICCU) and is recognized as a heterogeneous syndrome with variable etiology and clinical presentation that affects acute morbidity and mortality. AKI needs to be identified early and underlying causes must be treated Method: We performed a retrospective analysis of patient registry from Sardjito Cardiovascular Intensive Care (SCIENCE) between January 2021 and December 2021. This registry provided demographic data, risk factors, comorbidities, laboratory findings and survival outcomes. The KDIGO criteria were used to define AKI characterized by an increase in serum creatinine more or equal to 0.3 mg/dL in 48 hours, or an increase in serum creatinine more or equal to 1.5 times than previous value, or urine volume less than 0.5 mL/kg BW/hour for 6 hours. Univariate and multivariate data analyses were carried out. Results: This study included 428 patients with an incidence of AKI was 14,3 %. Univariate analysis showed that AKI was related to diabetes, acute heart failure, sepsis, APACHE score, SAPS, Sardjito score, MCARS, hemoglobin, leukocyte, and plasma albumin concentration. Furthermore, we did multivariate analysis and showed the independent predictor of AKI at ICCU admission is acute heart failure (OR 3.90; 95% CI 1.95–7.77; p <0.001), sepsis (OR 3.02; 95% CI 1.03-8.90; p 0.045) and high APACHE II score (OR 0.33; 95% CI 0.13-0.80; p 0.015). Conclusions: Acute heart failure, sepsis and high APACHE score at admission is independent predictors of AKI among critically ill in ICCU Sardjito General Hospital. The results of this study may contribute to the implementation of targeted therapies. This article has a related Erratum.